Root Tropisms: Investigations on Earth and in Space to Unravel Plant Growth Direction - Muthert, Lucius Wilhelminus Franciscus; Izzo, Luigi Gennaro; van Zanten, Martijn; Aronne, Giovanna (Frontiers in Plant Science, 2020)
Root tropisms are important responses of plants, allowing them to adapt their growth direction. Research on plant tropisms is indispensable for future space programs that envisage plant-based life support systems for long-term missions and planet colonization. Root tropisms encompass responses towards or away from different environmental stimuli, with an underexplored level of mechanistic divergence. Research into signaling events that coordinate tropistic responses is complicated by the consistent coincidence of various environmental stimuli, often interacting via shared signaling mechanisms. On Earth the major determinant of root growth direction is the gravitational vector, acting through gravitropism and overruling most other tropistic responses to environmental stimuli. Critical advancements in the understanding of root tropisms have been achieved nullifying the gravitropic dominance with experiments performed in the microgravity environment. In this review, we summarize current knowledge on root tropisms to different environmental stimuli. We highlight that the term tropism must be used with care, because it can be easily confused with a change in root growth direction due to asymmetrical damage to the root, as can occur in apparent chemotropism, electrotropism and magnetotropism. Clearly, the use of Arabidopsis thaliana as a model for tropism research contributed much to our understanding of the underlying regulatory processes and signaling events. However, pronounced differences in tropisms exist among species, and we argue that these should be further investigated to get a more comprehensive view of the signaling pathways and sensors. Finally, we point out that the Cholodny-Went theory of asymmetric auxin distribution remains to be the central and unifying tropistic mechanism after 100 years. Nevertheless, it becomes increasingly clear that the theory is not applicable to all root tropistic responses, and we propose further research to unravel commonalities and differences in the molecular and physiological processes orchestrating root tropisms.